2016
DOI: 10.1177/0363546516666352
|View full text |Cite
|
Sign up to set email alerts
|

Medial Patellofemoral Ligament Reconstruction Combined With Distal Realignment for Recurrent Dislocations of the Patella: 5-Year Results of a Randomized Controlled Trial

Abstract: Background: Tibial tubercle transfer (TTT) and medial patellofemoral ligament (MPFL) reconstruction have both shown, either in isolation or in combination, to provide improved patellofemoral joint (PFJ) stability. There are few studies that provide evidence that this remains true in the long term. Purpose: To compare the long-term results of patellar instability after TTT with and without MPFL reconstruction in 2 randomized groups. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 28 publications
5
38
0
1
Order By: Relevance
“…Damasena et al conducted a randomized controlled trial and compared between patients who underwent tibial tubercle transfer with lateral release, and patients who underwent tibial tubercle transfer, lateral release, and medial patellofemoral ligament reconstruction. 21 Similarly, they found that there was no significant difference between the two groups in terms of the rates of patellofemoral dislocation, the pain score, the Kujala score, the Tegner scores, and the time taken to return to work or sports. 21 They went on to conclude that there was insufficient evidence to conclude that the addition of medial patellofemoral ligament reconstruction to tibial tubercle transfer would result in few redislocations or reoperations.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Damasena et al conducted a randomized controlled trial and compared between patients who underwent tibial tubercle transfer with lateral release, and patients who underwent tibial tubercle transfer, lateral release, and medial patellofemoral ligament reconstruction. 21 Similarly, they found that there was no significant difference between the two groups in terms of the rates of patellofemoral dislocation, the pain score, the Kujala score, the Tegner scores, and the time taken to return to work or sports. 21 They went on to conclude that there was insufficient evidence to conclude that the addition of medial patellofemoral ligament reconstruction to tibial tubercle transfer would result in few redislocations or reoperations.…”
Section: Discussionmentioning
confidence: 96%
“…21 Similarly, they found that there was no significant difference between the two groups in terms of the rates of patellofemoral dislocation, the pain score, the Kujala score, the Tegner scores, and the time taken to return to work or sports. 21 They went on to conclude that there was insufficient evidence to conclude that the addition of medial patellofemoral ligament reconstruction to tibial tubercle transfer would result in few redislocations or reoperations. 21 With these, the current review has identified that isolated distal realignment procedures can lead to a significantly decreased rate of patellofemoral instability or maltracking and a significantly increased in number of patients with excellent or good outcomes postoperatively.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations